TECHNOLOGICAL TRENDS IN THE DEVELOPMENT OF THE PHARMACEUTICAL INDUSTRY - Kuvatov Jurʼatbek Dilshadbekovich (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
The pharmaceutical industry has long been at the forefront of innovation, with advancements in technology playing a pivotal role in shaping its trajectory. In recent years, the convergence of cutting-edge technologies has ushered in a new era of drug discovery, development, and manufacturing. This article explores the key technological trends driving progress in the pharmaceutical sector, highlighting their impact on efficiency, precision, and overall healthcare outcomes.